A semiautomated method to quantitatively assess osteolytic lesion volume and bone mineral density within acetabular regions of interest from CT. Issue 2 (30th April 2021) - Grace, Thomas M.; O'Rourke, Dermot; Robertson, Thomas; Perilli, Egon; Callary, Stuart; Taylor, Mark; Atkins, Gerald J.; Solomon, Lucian B.; Thewlis, Dominic
Abstract: The objectives of this study were to (1) develop a semiautomated method to obtain lesion volume and bone mineral density (BMD) in terms of Hounsfield units from pelvic computed tomography (CT) scans in three regions of interest, and (2) assess accuracy and reliability of the method based on cadaveric CT scans. Image artefacts due to metal implants reduce CT clarity and are more severe with more than one implant in situ. Therefore, accuracy and reliability tests were performed with varying numbers of total hip arthroplasties implanted. To test the accuracy of lesion size measurements, microcomputed tomography was used as a reference. Mean absolute error ranged from 36 to 284 mm 3 after five measurements. Intra‐ and inter‐operator reliability of the entire method was measured for a selection of parameters. All coefficient of variation values were good to excellent for CT scans of the native pelvic anatomy and a CT scans of the same pelvis with one and two implants in situ. Accuracy of quantifying lesion volume decreased with decreasing CT image clarity by 0.6%–3.6% mean absolute relative error. Reliability of lesion volume measurement decreased with decreasing CT clarity. This was also the case for reliability of BMD measurements in the region most disrupted by metal artefact. The presented method proposes an approach for quantifying bone loss which has been proven to be accurate, reliable, and clinically applicable.